Development of water-based gelling system for high-temperature wellbore cleanout operation - Ismail, Jamil; Ab. Rahim, Mohd Hasbi; Roslan, Rasidi; Mohd Halimi, Abdul Aziz
The concerns on finding an excellent gelling fluid for high temperature reservoir have dragged many attentions for the improvement of conventional gelling fluid. In the present study, cationic diutan gum (CDG) was modified to enhance its thermal and viscosity properties by attaching quaternary amine group to hydroxyl group of diutan gum (DG). N-(3-chloro-2-hydroxypropyl) trimethyl ammonium chloride (CHPTAC) was used as the source of the quaternary amine group. The effect of differing concentration of CHPTAC with the presence of NaOH upon DG was studied. The efficiency of the modification was studied using Fourier transform infrared (FTIR), Field emission scanning electron microscope (FESEM), thermal analysis and viscosity analysis. The viscosity analysis shows that the viscosity increased as the amount of CHPTAC used increased. Moreover, from the thermal analyses, the data indicate that the cationic gum has much better thermal resistance compare with the unmodified gum. Therefore, the modification of DG by attaching the quaternary amine group on the hydroxyl group of DG has presented a promising alternative for the exploration of high temperature reservoir. In addition, the used of modified biopolymer like DG is a sustainable substitute for environmentally friendly gelling agent for oil and gas industry.